Sex-biased gene expression and sequence conservation in Atlantic and Pacific salmon lice (Lepeophtheirus salmonis). (December 2016) - Poley, Jordan; Sutherland, Ben; Jones, Simon; Koop, Ben; Fast, Mark
Abstract Background Salmon lice, Lepeophtheirus salmonis (Copepoda: Caligidae), are highly important ectoparasites of farmed and wild salmonids, and cause multi-million dollar losses to the salmon aquaculture industry annually. Salmon lice display extensive sexual dimorphism in ontogeny, morphology, physiology, behavior, and more. Therefore, the identification of transcripts with differential expression between males and females (sex-biased transcripts) may help elucidate the relationship between sexual selection and sexually dimorphic characteristics. Results Sex-biased transcripts were identified from transcriptome analyses of threeL. salmonis populations, including both Atlantic and Pacific subspecies. A total of 35-43 % of all quality-filtered transcripts were sex-biased inL. salmonis, with male-biased transcripts exhibiting higher fold change than female-biased transcripts. For Gene Ontology and functional analyses, a consensus-based approach was used to identify concordantly differentially expressed sex-biased transcripts across the three populations. A total of 127 male-specific transcripts (i.e. those without detectable expression in any female) were identified, and were enriched with reproductive functions (e.g. seminal fluid and male accessory gland proteins). Other sex-biased transcripts involved in morphogenesis, feeding, energy generation, and sensory and immune system development and function were also identified. Interestingly, as observed in model systems, male-biasedL. salmonis transcripts were more frequently without annotation compared to female-biased or unbiased transcripts, suggesting higher rates of sequence divergence in male-biased transcripts. Conclusions Transcriptome differences between male and femaleL. salmonis described here provide key insights into the molecular mechanisms controlling sexual dimorphism inL. salmonis . This analysis offers targets for parasite control and provides a foundation for further analyses exploring critical topics such as the interaction between sex and drug resistance, sex-specific factors in host-parasite relationships, and reproductive roles withinL. salmonis .